Integral representation of a solution of the Cauchy problem for a degenerating hyperbolic equation with retarded argument - Zarubin, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
By using the method of integral equations, we prove the existence and uniqueness of a regular solution of the Cauchy problem for a degenerating hyperbolic equation with retarded argument.